Dear People would someone be able to explain in more detail this problem. I can't follow the answer.(adsbygoogle = window.adsbygoogle || []).push({});

a=alpha (its a superscript)

Y/L =(K/L)^α (E)^1-α

These are steps to get to final answer

Y/L=K^a/L^-a * E/E^a Step 1 - rewrite

Y=K^a/L^a * EL/E^a Step2 multiply by L

How did L^-a became L^a after multiplying by L. Is this rule of negative exponent??

Now with some algebra, we can rearrange it; Step 3

Y=K^a * EL/(EL)^a

please help me understand in detail how you end up with K^a after multiplying by L. How can L cancel out L^a

Answer

Y=K^a (EL)^1-a

Gog Bless

**Physics Forums - The Fusion of Science and Community**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Y/l =(k/l)^α (e)^1-α

**Physics Forums - The Fusion of Science and Community**